Isolation and characterization of 2, 2-Dichloropropionate degrading bacteria from Gebeng industrial area - Firdausi Aliyu, 1988-, author; Fahrul Zaman Huyop, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Sains (Bioteknologi)) - Universiti Teknologi Malaysia, 2017